Deformities in reared cobia, Rachycentron canadum L. and grouper, Epinephelus marginatus, in São Paulo state coast, Brazil: Case report - Filho, J.R. Engrácia [UNESP]; Shimada, M. T. [UNESP]; Yunis-Aguinaga, J. [UNESP]; Ramos-Espinoza, F. C. [UNESP]; Moraes, F. R. [UNESP]; Moraes, J. R.E. [UNESP] (FapUNIFESP (SciELO), 2018)
Skeletal deformities are frequent problems in cultured fish populations due mainly to unfavorable abiotic conditions, inappropriate nutrition, and genetic factors. These may cause erratic swimming, decrease of conversion rate, growth, and market value. The aim of this case report was to present the occurrence of deformities in juvenile cobia and groupers from an offshore marine farm in Ilhabela, São Paulo, Brazil. Nine cobias and seven juvenile groupers, that presented deformities, were euthanized and fixed in 10% formaldehyde. They were tagged, processed, and stained with Alcian Blue (AB) and Alizarin Red-S (ARS) for visualization of cartilage and bone tissue, respectively. After evisceration, radiographic examination was performed. The deformities observed in cobia were atrophy of the operculum, disorganization of the gill lamellae, deformity of the lower jaw, kyphosis, and scoliosis. Groupers presented lower jaw deformity and saddleback syndrome. The farm studied in this case report had poor management standards, fed commercial feed for freshwater herbivorous fish and cooked sardines, high inbreeding and absence of adequately trained professionals to manage these species. The sum of these factors must have directly influenced the appearance of these deformities. It is necessary to control this situation to minimize the incidence of malformations that have economic impacts to farmers.

As deformidades esqueléticas são problemas frequentes em populações de peixes cultivados devido, principalmente, a condições abióticas desfavoráveis, nutrição inapropriada e fatores genéticos. Estas podem causar natação errática, diminuição do índice de conversão, do crescimento e do valor no mercado. O objetivo deste relato de caso foi apresentar a ocorrência de deformidades em cobias e garoupas juvenis provenientes de uma fazenda marinha em sistema offshore, em Ilhabela, São Paulo, Brasil. Nove cobias e sete garoupas juvenis, que apresentavam deformidades, foram sujeitos à eutanásia e fixados em formol a 10%. Os espécimes foram registrados, processados e corados com Alcian Blue (AB) e Alizarin Red-S (ARS) para visualização de tecido cartilaginoso e ósseo, respectivamente. Os peixes foram eviscerados para o exame radiográfico. As deformidades observadas em cobia foram: atrofia do opérculo, desorganização das lamelas branquiais, deformidade do maxilar inferior, cifose e escoliose. As garoupas apresentaram deformidade do maxilar inferior e síndrome de Saddleback. Os peixes deste relato de caso estiveram sob manejo deficiente, alimentados com ração comercial para peixes herbívoros de água doce e sardinhas cozinhadas, alta consanguinidade e ausência de profissionais adequadamente treinados para o manejo dessas espécies. A soma desses fatores influenciou diretamente na aparição dessas deformidades, precisando ser controlados para minimizar a incidência de malformações que tenham impacto econômico para os produtores.
Keywords: Atrofia do opérculo; Cifose; Escoliose; Kyphosis; Operculum atrophy; Saddleback syndrome; Scoliosis; Síndrome de saddleback